The role of Shiite clerics during the Safavid state (1501-1722). - Ali, Jafar; Osman, Nazim (Humanities Journal of University of Zakho, 2023)
This study deals with the political situation in Iran during the Safavid authority and the declaration of Shiism doctrine as the official state religion by Shah Ismael I (1501-1524). It presents how the Shiism was formed and strengthened, and also deals with the appearance of Shia religious men in the political and social fields from the declaration of the Safavid state until the end of their authority. Additionally, the religious changes and the relations of the Safavid rulers with religious men are investigated.The religious policy of Shah Tahmasp I (1524-1577) manifested in bringing a great number of scientists and Shia religious men from the Arab homeland to Iran. The Shah used those religious men in writing and publishing Shia jurisprudence books and expanding the Shiism. The fundamentals of Shiism was written during the reign of this Shah, and the authority of religious men reached the top. Besides, a great number of posts and religious titles were created at the reign of Shah Tahmasp. Another part of this study tackled the arrival of Ismael II (1576-1577) and his policy to weaken the authority of Shia religious men, and pay attention to the Sunni doctrine.Moreover, the study presented the religious policy of Shah Abbas the Great (1587-1622), who was the strongest Safavid Shah, and his attempt to remove the Qizal- Bash Sufis. He also reduced the political role of religious men and tried to establish a strong authority away from religious men. The authority of the religious men increased after Shah Abbas the Great, especially at the final reign of the Safavid authority at the reign of Hussein Al-Safawi (1694-1722). During that period, the Safavid state was completely controlled by religious men. At the reign of Shah Hussien, the Safavid authority became under the control of Mala (Mahmoud Baqir Majlisi) , who practiced a great deal of violence against other religions, especially the Sunni and Zaradashti religions.The degree and posts of religious men, their social position, class and their influence on the Iranian society will be investigated. The study also will discuss the role of religious men in the field of education, and how Sharia courts were managed by religious men, because these two important and influential points were the reason behind strengthening the authority of religious men as it was completely supervised by them.